Exploring the ontogenetic development of the inner ear in Aardvarks. Issue 5 (21st December 2020) - Berlioz, Emilie; Cornette, Raphaël; Lenoir, Nicolas; Santin, Mathieu D.; Lehmann, Thomas
Abstract: The aardvark is the last living Tubulidentata, an order of afrotherian mammals. Afrotheria is supported strongly by molecular analyses, yet sparingly by morphological characters. Moreover, the biology of the aardvark remains incompletely known. The inner ear, and its ontogeny in particular, has not been studied in details yet, though it bears key ecomorphological characters and phylogenetical signal. The aim of this study is to decipher and discuss the ontogenetic development of the different areas of the inner ear of Orycteropus afer . We focused in particular on their relative size and morphological rates of development. Specimens were scanned with 3D imaging techniques. 3D and 2D geometric morphometrics coupled with qualitative descriptions of the petrosal ossification allowed us to evidence several stages through development. Based on our sample, the cochlea is the first structure of the inner ear to reach adult size, but it is the last one to acquire its adult morphology close to parturition. In contrast, after a delayed growth spurt, the semicircular canals reach their mature morphology before the cochlea, concomitantly with the increase of petrosal ossification. The ontogeny of the aardvark inner ear shows similarities with that of other species, but the apex of the cochlea presents some autapomorphies. This work constitutes a first step in the study of the ontogeny of this sensorial organ in Afrotheria. Abstract : X ray Micro Tomography coupled with Magnetic Resonance Imaging allowed us to explore the modalities of the acquisition of the mature shape of the inner ear of Orycteropus afer as well as to consider for the first time inter‐individual inner ear variability among adult aardvarks. The developmental steps for O. afer inner ear were compared with that of other vertebrates and we showed that it presents similarities with the inner ear ontogeny of other mammals but also peculiarities.